Effect of Village Government HR Competence and IT use on Accountability of Village Fund Management in Pringsewu - Nabella Ariantika; Saring Suhendro (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates the influence of village government human resource (HR) competence and information technology (IT) utilization on the accountability of village fund management, with empirical evidence drawn from villages in Pringsewu Regency, Indonesia. The research addresses critical concerns about the underperformance and misuse of village funds, often linked to weak HR capabilities and limited IT adoption. The primary objective is to examine how HR competence and IT usage affect financial accountability in village fund management. Utilizing a quantitative approach, this study surveyed 91 village officials across 13 villages using a structured questionnaire, applying multiple linear regression analysis for hypothesis testing. Findings reveal that both HR competence and IT utilization significantly and positively influence accountability, suggesting that skilled personnel and effective use of digital systems enhance transparency and financial governance. The results support the Technology Acceptance Model (TAM) and stewardship theory, emphasizing the importance of reliable personnel and technological systems in public financial management. The study concludes that strengthening human resource capacity and advancing IT infrastructure are critical steps in ensuring accountable village fund management, especially in rapidly developing regions such as Pringsewu Regency.